EFEK PENAMBAHAN EKSTRAK KASAR ENZIM BROMELIN DALAM PAKAN TERHADAP PENAMPILAN PRODUKSI - E. Fitasari; Soenardi Soenardi (BUANA SAINS, 2012)
Abstract The research about bromeline crude extract was conducted to determine the giving of enzyme on broiler production performance (consumption, weight gain, feed convertion ratio and income over feed cost). This research used 5 treatments: P0 (control), P1 (bromeline crude extract 2% w/w), P2 (bromeline crude extract 4% w/w), P3 (bromeline crude extrac 6%), and P4 (bromeline crude extrac 8%). This study was carried out in Randomized Complete Design. The significant influence, was be tested with Least Significant Difference Test. The result showed that the treatments didt’n gave significant difference (p>0.05) on consumption, weight gain, feed convertion ratio and very significant effect (p